PEMBERDAYAAN DAN PENGEMBANGAN POTENSI PURA PENGUKUR KABUPATEN GIANYAR, BALI SEBAGAI DESTINASI WISATA SEJARAH - Ni Putu Rahayu Mahadewi; Ni Putu Yuniarika Parwati; I Nyoman Bayu Pramartha; I Nyoman Kartika Yasa (LPPM Universitas PGRI Mahadewa Indonesia, 2022)
Bali Island is one of the islands in Indonesia which has a variety of natural beauty and historical heritage that is very real and can still be found today. Gianyar Regency is one of the areas where there are various historical heritage sites and has been recognized by the Bali Provincial Cultural Heritage Preservation Agency. The number of relics that can be found is inseparable from the location of the area which is near the river channel area (DAS), namely the Pekerisan and Petanu watersheds. In prehistoric times, this area was believed to have been used to establish a kingdom as his territory and also to become a hermitage area. With the discovery of relics around the watershed area, this will encourage the development and empowerment of historical remains which in the future can be used as historical tourist destinations. One of them is the Measurement Temple which is on the west side of the Pakerisan river. In community service activities by History Education students using qualitative methods based on literature, observation and interviews. Through the triangulation method in this study will be able to reveal the purpose of this study